Integrative Computational Analysis of Bioactive Benzoquinones: CDK Binding, Toxicity, and Pharmacokinetics - Hakeem, Israa Jameel; Haque, Shahnaz; Rafeeq, Misbahuddin; Kamal, Mohammad Azhar; Bakhsh, Tahani; Almutairi, Abdulrahman; Alniwaider, Rashed Ahmed; Thani, Ali Bin; Alam, Qamre (International Journal of Pharmaceutical Investigation, 2026)
Background Cyclin-Dependent Kinase is a member of cell cycle regulatory proteins and active in the formation of tumor in breast. Three active compounds Anthraquinone, Emodin and Kaempferol are evaluated using DFT calculations, ADMET predictions, toxicity profiling, and molecular docking against CDK6 (5L2S) to predict the potential drugs against this proptien. Purpose The purpose of this study was to evaluate Anthraquinone, Emodin, and Kaempferol as potential CDK6 inhibitors using integrated in silico methods (DFT, ADMET/toxicity profiling, and molecular docking). It aimed to identify the most promising scaffold by correlating electronic reactivity and binding affinity with predicted pharmacokinetic and safety profiles. Materials and Methods The compounds are optimized in silico with the help of Gaussian16 suit of program and functional B3LYP with basis set 6-311G(d,p). Pharmacokinetic properties are analysed with ADMET and Binding affinity with AutoDock Vina Discovery Studio Visualizer. Results FMO analysis showed that Emodin has the smallest energy gap, indicating greater reactivity, while Anthraquinone and Kaempferol are comparatively more stable. MEP maps show that oxygen atoms are key reactive sites, with Kaempferol showing the highest electronegative potential. ADMET results revealed that Anthraquinone has good BBB penetration but high carcinogenic risk and rapid clearance, Emodin shows strong oral bioavailability with mutagenicity and hepatotoxicity concerns, and Kaempferol demonstrates the longest half-life with low CNS penetration. Docking studies confirmed Emodin as the strongest binder (-9.0 kcal/mol) through hydrogen bonding and hydrophobic interactions, while Kaempferol showed moderate binding, and Anthraquinone showed strong but less favourable binding due to toxicity. Conclusion Our computational approaches show that Emodin predicted as the most promising CDK6 inhibitor scaffold, Kaempferol provides balanced pharmacokinetic potential and Anthraquinone could be limited by safety risks.
Keywords: ADMET; Bioactive Compounds; Cyclin-Dependent Kinase-6; Molecular Docking; Pharmacokinetic; Toxicity